Leveraging Artificial Intelligence for Construction Project Scheduling - Akhmedov Alisher (Genius Journals, 2023)
This article explores the transformative role of Artificial Intelligence (AI) in construction project scheduling. It highlights how AI-powered solutions can enhance efficiency, reduce delays, and optimize resource allocation in construction projects. By harnessing the capabilities of machine learning and predictive analytics, the construction industry can revolutionize project management and meet the growing demands for faster, more cost-effective, and sustainable construction practices.
Keywords: Artificial Intelligence; construction project scheduling; optimization; efficiency